Exploration of Elementary School Geometry in Hand Movements of the Bojonegoro Kembang Kahyangan Dance - Erika Dewi Agustin; Neni Mariana (International Journal of Elementary Education, 2025)
Problems in mathematics learning in elementary schools are often abstract, causing students to have difficulty understanding geometric concepts. This study aims to explore the geometric concepts contained in the hand movements of the Kembang Kahyangan Bojonegoro dance. The approach used is qualitative with an ethnographic method. The researcher served as the primary instrument, with additional instruments including observation sheets, interview guidelines, and documentation. Data collection was conducted through literature review, observation, interviews, and documentation at the Sanggar Tari Angling Darma Bojonegoro dance studio. The research subjects were Kembang Kahyangan dance instructors selected using purposive sampling. Data analysis was conducted based on Spradley's model. The results of the study indicate that various geometric concepts can be found in the basic movements and beyond the basic movements of the Kembang Kahyangan dance. These concepts include acute angles, right angles, obtuse angles, and straight angles, as well as two-dimensional shapes such as triangles, rectangles, and trapezoids. These findings reveal a strong connection between dance art, geometric concepts, and learning outcomes for phases A-C at the elementary school level. Thus, the application of the ethnomathematics approach can serve as a concrete, contextual, and meaningful learning resource for students.